Tumor mamário canino: estudo in vitro, imunomarcação e ação da doxorrubicina - Lima, Silmara Sanae Sakamoto de [UNESP] (2014)
Canine mammary tumors represent a high casuistry in veterinary oncology and few studies with cell culture are being employed, mainly with drug application. The purpose was to establish and standardize the cell culture of canine mammary tumors for in vitro efficacy of doxorubicin and to correlate the immunostaining of vimentin, cytokeratin, p53 and HER-2, in paraffin sections of original tumor and the cell cultures derivated. Benign mixed tumor, complex carcinoma, simple carcinoma and espinocelular carcinoma were cultivated from explants and the cells originated were incubated with doxorubicin in different concentrations (control-0.25-0.50-0.75-1.0-2.0μM). The percentual of viable cells were determined by the Trypan blue dye exclusion test and for immunoexpression, the immunohistochemistry was performed for the primary tumor and immunofluorescence, for the cells. A total of 39 tumor samples were collected and, 40% were cultivated up to fifth passages. A different imunnoexpression was observed between methodologies with higher expression at vimentin, p53 and HER-2 groups. It was observed that doxorubicin presented an elevated efficacy in canine mammary cell culture but without difference among the histological groups and each sample presented an individual responsiveness for the same treatment. So, it can be concluded that it was possible to realize a primary cell culture with a simple culture medium formulation; gene expression profiles in tumor tissue and cell culture derived from those tumors are better designated than immunoexpression tests and higher the concentration of doxorubicin, lower the cell viability